REACTIVATION POTENCY OF THE ACETYLCHOLINESTERASE REACTIVATOR OBIDOXIME IS LIMITED - Kuca, Kamil; Musilek, Kamil; Pohanka, Miroslav; Dohnal, Vlastimil; Patocka, Jiri (Biomedical papers, 2009)
Background: Obidoxime is the only one reactivator of acetylcholinesterase (AChE) approved in Czech Republic for the treatment of nerve agent and pesticide poisonings for civilian sector. Due to the fact that misuse of nerve agents by terrorists or by an accidental poisoning by farmers is possible, re-evaluation of its universality is needed. It is also needed by the fact that clinical findings considering this oxime are controversial.Aim: In this study, we wanted to summarize if obidoxime is a universal reactivator or if its reactivation potency in case of some organophosphorus inhibitors is limited.Method: Using our in vitro method, rat brain AChE was inhibited by eleven organophosphorus AChE inhibitors and then reactivated by obidoxime. Results and Conclusion: It was found that obidoxime could not be termed as universal antidote. Due to this, development of new promising candidates as replacement of obidoxime is recommended.
Keywords: Keywords: Obidoxime/Acetylcholinesterase/Nerve agent/Pesticide/Antidote/Reactivator/Oxime